2012
DOI: 10.1074/jbc.m112.351254
|View full text |Cite
|
Sign up to set email alerts
|

Binding Modes of Zaragozic Acid A to Human Squalene Synthase and Staphylococcal Dehydrosqualene Synthase

Abstract: Background: Fungal metabolites, zaragozic acids, are potent inhibitors against squalene synthase and S. aureus dehydrosqualene synthase. Results: Here we reported the zaragozic acid A binding mode for the head-to-head prenyltransferase drug targets. Conclusion: Zaragozic acid A presents an unexpected binding mode from the cyclopropyl-containing intermediate in both enzymes. Significance: Our structures provide a structural basis for development of potential drugs for hyperlipidemias and bacterial infection tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 39 publications
0
57
0
Order By: Relevance
“…This finding indicated that compounds inhibiting the production of staphyloxanthin could be a source of new anti-infectious agents against MRSA. On the basis of this concept, BPH-652, 7 zaragozic acid, 9 7-benzyloxyindoles 10 and flavones 11 were reported to be inhibitors of staphyloxanthin production. We started to search for such inhibitors from natural sources using our established screening system, 12 leading to the discovery of tylopilusins 13 and citridone A and its derivatives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding indicated that compounds inhibiting the production of staphyloxanthin could be a source of new anti-infectious agents against MRSA. On the basis of this concept, BPH-652, 7 zaragozic acid, 9 7-benzyloxyindoles 10 and flavones 11 were reported to be inhibitors of staphyloxanthin production. We started to search for such inhibitors from natural sources using our established screening system, 12 leading to the discovery of tylopilusins 13 and citridone A and its derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…We started to search for such inhibitors from natural sources using our established screening system, 12 leading to the discovery of tylopilusins 13 and citridone A and its derivatives. 14 Continuing our screening program, new compounds designated graphiumins A (1) to H (8), along with two structurally related known bisdethiobis(methylthio)-deacetylaranotin (9) 15 and bisdethiobis(methylthio)-deacetylapoaranotin (10), 15 were isolated from the culture broth of the marine-derived fungus Graphium sp. OPMF00224 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Citridone A (1) and its 11 derivatives (7,11,14,15,16,17,19,20,21,27 and 29) were synthesized. 4 Derivatives 11, 17 and 21 (enantiomer of 1) were prepared as shown in Chart 1, according to the total synthesis of 1 we achieved previously.…”
Section: Resultsmentioning
confidence: 99%
“…1, 3 All experimental procedures for the synthesis of compounds (7,11,14,15,16,17,19,20,21,27 and 29), including citridone A (1), are summarized in Supplementary Information. (5aS,8R,8aS)-5a,7,8-Trimethyl-4-phenyl-2,5a,8,8a-tetrahydro-1H-cyclopenta [4,5] furo [3,2- (5aS,8R,8aS)-5a,8-Dimethyl-1-oxo-4-phenyl-2,5a,8,8a-tetrahydro-1H-cyclopenta [4,5] : 190.0, 164.3, 162.9, 151.8, 147.2, 134.7, 133.0, 128.5, 127.5, 127.3, 112.3, 110.8, 101.3, 56.8, 42.4, 25.1, 20 (5aS,8R,8aS)-7-(Hydroxymethyl)-5a,8-dimethyl-4-phenyl-2,5a,8,8a-tetrahydro-1H-cyclopenta [4,5]furo [3,2-c]pyridin-1-one (19). (4bS,5R,7aS)-5,6,7a-Trimethyl-3-phenyl-4b,5-dihydro-1H-cyclopenta [4,5]furo [2, 3-b]pyridin-4(7aH)-one (20). (5aR,8S,8aR)-5a,7,8-Trimethyl-4-phenyl-2,5a,8,8a-tetrahydro-1H-cyclopenta [4,5] furo [3,2- (5aS*,8aS*)-4-Phenyl-2,5a,8,8a-tetrahydro-1H-cyclopenta [4,5]furo [3,2- Assay for miconazole-potentiating activity against C. albicans using paper disks C. albicans ATCC 64548 was inoculated into a 50-ml test tube containing 10 ml seed medium (potato extract containing peptone 0.50% and glucose 1.0%), and was grown for 24 h on a rotary shaker.…”
Section: Experimental Procedures and Characterization Datamentioning
confidence: 99%
“…38) This finding indicated that inhibitors of STX production could be new anti-infective drugs against MRSA. Several known compounds, BPH-652, 38) zaragozic acid, 39) 7-benzyloxyindoles 40) and flavones, 41) were reported to inhibit STX production. Among these, BPH-652, an inhibitor of squalene synthase, proved in vivo efficacy, blocking the infection of S. aureus in the host mice.…”
Section: Screening For Inhibitors Of Mrsa Yellow Pigment Productionmentioning
confidence: 99%